Exploring the pull and push underlying problem video game use: A Self-Determination Theory approach. (1st December 2018) - Mills, Devin J.; Milyavskaya, Marina; Mettler, Jessica; Heath, Nancy L.
Abstract: Research has revealed that the push to engage in video games is in part the perception that they satisfy three basic psychological needs (competence, autonomy, relatedness). However, the pull toward a problematic style of video game engagement based on Internet Gaming Disorder symptomatology has been found to be explained in part by the daily frustration of these same needs. Currently, these two areas of gaming research have been conducted within separate studies. Therefore, the objective of the present study was to bridge these two theoretically compatible areas of research in exploring the interaction between gaming need satisfaction and daily need frustration in explaining problem video game use and gaming frequency. An online sample of 922 adults (59.1% males; M age = 23.53 years; SD = 6.84) were recruited. Results revealed both gaming need satisfaction and daily need frustration positively contributed to gaming frequency and problem video game use accounting for 19.7% and 23.5% of their respective variances. Furthermore, gaming frequency and problem video game use were highest when both gaming need satisfaction and daily need frustration were high. The implications of these results are discussed within the context of current research and strengths-based clinical approaches.